Identifying key components of a global conceptual framework for adolescent nutrition: Review, nominal group technique and youth co-design - Marion L Roche; Deepika Sharma; Sarah Kehoe; Sara Estecha-Querol; Catharine A K Fleming; Amir A Samnani; Milca J Cameseria; Dipty Chowdhury; Webster Isheanopa Makombe; Amanda Murungi Eunice; Muhammad Sarim Raza; Miriam Shindler; et al. (BMJ Global Health)
Background Optimal nutrition during adolescence is critical to growth and development. While several adolescent nutrition frameworks exist, a comprehensive reference framework is needed, which reflects the priorities and views of young people and guides action to improve adolescent nutrition. We believe that partnering with young people is key to enabling agency and empowering change. This collaborative project between the Global Adolescent Nutrition Network (GANN) and youth partners aimed to develop a conceptual and actionable framework for adolescent nutrition. This paper presents the methods used to identify the need for and to prioritise the key components of a new framework.Methods A literature review was conducted to identify and summarise available frameworks for adolescent nutrition (10–19 years). GANN members (N=7) and youth partners (N=4, 18–26 years) used nominal group technique (NGT) methodology to reach consensus on: (1) key characteristics, strengths and limitations of available frameworks; (2) key characteristics of an ideal framework; (3) the best available framework and (4) the need for a new framework.Results NGT participants listed 37 strengths and limitations of the 15 frameworks identified in the review. These were classified into three themes: theory, usability and visibility. According to NGT participants, the most important (‘top’) theoretical features of an ideal framework were considering all forms of malnutrition’ and including all levels of influence in adolescent nutrition’. Most top usability and visibility features were applicable at global, regional and country levels, and a clear structure to depict levels of influence, respectively. The Innocenti Framework was deemed the best available framework. Most of the participants (90%) agreed that a new framework was needed. Youth partners advocated for greater representation of youth voices in frameworks and programmes related to adolescents. The salient features of the new framework, reached by consensus, emphasise an action-oriented approach that provides practical guidance to improve adolescent nutrition rather than solely explaining its determinants. It will be designed to be adaptable to different contexts, ensuring its visual design, language and content are accessible and engaging for a broad range of stakeholders.Conclusion Through a novel youth codesign process, we identified key components to inform the development of a new conceptual framework to improve adolescent nutrition. While no new framework is presented in this article and is part of ongoing work, these findings provide guidance for future efforts to create a framework that can effectively inform actions and investments in global adolescent nutrition.